Comparing the diurnal and seasonal variabilities of atmospheric and surface urban heat islands based on the Beijing urban meteorological network. Issue 4 (17th February 2017) - Wang, Kaicun; Jiang, Shaojing; Wang, Jiankai; Zhou, Chunlüe; Wang, Xiaoyan; Lee, Xuhui
Abstract: This study compared the diurnal and seasonal cycles of atmospheric and surface urban heat islands (UHIs) based on hourly air temperatures ( Ta ) collected at 65 out of 262 stations in Beijing and land surface temperature ( Ts ) derived from Moderate Resolution Imaging Spectroradiometer in the years 2013–2014. We found that the nighttime atmospheric and surface UHIs referenced to rural cropland stations exhibited significant seasonal cycles, with the highest in winter. However, the seasonal variations in the nighttime UHIs referenced to mountainous forest stations were negligible, because mountainous forests have a higher nighttime Ts in winter and a lower nighttime Ta in summer than rural croplands. Daytime surface UHIs showed strong seasonal cycles, with the highest in summer. The daytime atmospheric UHIs exhibited a similar but less seasonal cycle under clear‐sky conditions, which was not apparent under cloudy‐sky conditions. Atmospheric UHIs in urban parks were higher in daytime. Nighttime atmospheric UHIs are influenced by energy stored in urban materials during daytime and released during nighttime. The stronger anthropogenic heat release in winter causes atmospheric UHIs to increase with time during winter nights, but decrease with time during summer nights. The percentage of impervious surfaces is responsible for 49%–54% of the nighttime atmospheric UHI variability and 31%–38% of the daytime surface UHI variability. However, the nighttime surface UHI was nearly uncorrelated with the percentage of impervious surfaces around the urban stations. Key Points: Atmospheric and surface urban heat islands (UHIs) were compared in Beijing The nighttime UHIs referenced to rural croplands exhibited obvious seasonal cycles but not for those referenced to mountainous forests The impervious surface ratio explains 49%–54% of the nighttime atmospheric UHIs and 31%–38% of the daytime surface UHI